2019
DOI: 10.1111/aje.12641
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic associations reveal clan size and social network structure in the fission–fusion society of spotted hyaenas

Abstract: Estimating the size and dynamics of populations is of paramount importance in ecology.In species with uniquely marked individuals, capture-recapture methods can be used to establish population size and to explore associations between individuals. However, very few studies have used cameras traps to focus on group composition in social carnivores, despite being of particular interest in species characterised by "fission-fusion" formation of sub-groups. Here, we provide estimates of (a) population size, (b) dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
(116 reference statements)
0
18
0
Order By: Relevance
“…In wild lions, Casetta et al (2021) did not investigate if a yawn actually occurred in coincidence with a changing in the behavioural status of the first yawner, although they demonstrated that being infected by a companion's yawn provoked an alignment of the activities between the first and the second yawner. Considering the high levels of cohesion and cooperation typical of spotted hyaenas, we can reasonably hypothesise that yawn contagion can be an adaptive phenomenon also in this species and that it could help synchronise activities, especially between females due to their leading role in the groups (Stratford and Périquet 2019;Vullioud et al 2019). This hypothesis would be worth to be investigated in the future by enlarging the datasets both on males and females and embracing the different subgroups deriving from the fission-fusion events typical of the species (Strauss et al 2021).…”
Section: Discussionmentioning
confidence: 95%
“…In wild lions, Casetta et al (2021) did not investigate if a yawn actually occurred in coincidence with a changing in the behavioural status of the first yawner, although they demonstrated that being infected by a companion's yawn provoked an alignment of the activities between the first and the second yawner. Considering the high levels of cohesion and cooperation typical of spotted hyaenas, we can reasonably hypothesise that yawn contagion can be an adaptive phenomenon also in this species and that it could help synchronise activities, especially between females due to their leading role in the groups (Stratford and Périquet 2019;Vullioud et al 2019). This hypothesis would be worth to be investigated in the future by enlarging the datasets both on males and females and embracing the different subgroups deriving from the fission-fusion events typical of the species (Strauss et al 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Camera traps were deployed in the field by 2007 for brown hyenas (Thorn et al 2009 ), 2007–2008 for striped hyenas (Gupta et al 2009 ; Harihar et al 2010 ; Singh et al 2010 ; Athreya et al 2013 ), and 2008 for aardwolves (O’Brien and Kinnaird 2011 ). Photographic capture–recapture has been used to estimate the density of spotted hyenas in many countries throughout their geographic range, such as Congo (Henschel et al 2014 ; Bohm 2015 ), Uganda (Braczkowski et al 2022 ), Kenya (O’Brien and Kinnaird 2011 ), Botswana (Rich et al 2019 ; Vitale et al 2020 ), Namibia (Stratford et al 2020 ), and South Africa (de Blocq 2014 ). In rare cases in which all study animals were known from extensive long-term direct observations, researchers derived precise counts of spotted hyenas within their study area (rather than using capture–recapture methods to estimate abundance; Watts and Holekamp 2009 ; Green et al 2018 ), but extensive direct observations yield a better return-on-investment for behavioral studies than for population estimation (de Blocq 2014 ).…”
Section: Past and Present Use In Basic Researchmentioning
confidence: 99%
“…Camera trapping has scarcely been used to study spotted hyena sociality, but a recent pioneering study (Stratford et al 2020 ) suggests that camera traps can be used to shed light on the diversity in group composition and dynamics within this species. Clan size of spotted hyenas is highly variable, ranging from six to over a hundred individuals (Kruuk 1972 ; Green et al 2018 ), depending on environmental factors (Stratford et al 2020 ).…”
Section: Past and Present Use In Basic Researchmentioning
confidence: 99%
“…Ongava Research Centre (ORC) in northern Namibia faces a similar challenge. Here, dozens of cameras are deployed regularly on a private reserve to study wildlife ecology and distributions (Edwards et al 2018;Stratford et al 2019), to assess camera utility and performance (Stratford and Naholo 2017), and to assist with wildlife management questions on the reserve. For example, over the last decade approximately 50 cameras have been set at permanent waterholes every year as part of the reserve's wildlife population monitoring programme, routinely generating upwards of 800 000 images within only a few weeks.…”
Section: Introductionmentioning
confidence: 99%